The Repeatable Battery for the Assessment of Neuropsychological Status, While Useful for Measuring Cognitive Changes in Manifest Huntington Disease, May Show Limited Utility in Premanifest Disease. Issue 3 (13th September 2022) - Mustafa, Andrea I.; Corey-Bloom, Jody; Beltran-Najera, Ilex; Snell, Chase; Castleton, Jordan; Smith, Haileigh; Gilbert, Paul E.
Abstract : Background: The Repeatable Battery for the Assessment of Neuropsychological Status (RBANS) is a brief, standardized neuropsychological test that assesses several areas of cognitive function. Recent studies, although sparse, have examined the use of the RBANS to detect cognitive deficits in individuals with manifest Huntington disease (HD); however, no studies have investigated its utility to detect cognitive deficits in individuals with premanifest HD (PreHD), where cognitive symptoms are thought to be more subtle. Objective: To assess cognitive deficits in individuals with HD, particularly in individuals with PreHD, using an easily administered, brief but comprehensive, neuropsychological test. Method: We administered the RBANS to 31 individuals with HD, 29 individuals with PreHD, and 22 healthy controls (HC) at an academic HD clinical research center and collected RBANS Total, Index, and subtest scores for group comparisons. Results: The HD group had significantly lower RBANS Total, Index, and subtest scores than the HC. The PreHD group had significantly lower RBANS Total scores and Coding subtest scores than the HC, but no other significant group differences were identified. Conclusion: Our results substantiate previous findings of significant impairment on the RBANS in individuals with HD. In addition, we are the first to demonstrate that, although the RBANS can identify deficits in psychomotor speed and information processing in individuals with PreHD, it does not appear to have the ability to detect impairment in any additional cognitive domains in individuals with PreHD.